Juegos predeportivos en el desarrollo psicomotor en niños - Carchi Chacha, Mónica Alexandra (2024)
The present research work titled "Pre-Sport Games in the Psychomotor Development of Sixth- Grade Children at the Pensionado Americano International School for the 2024 Academic Year" aims to determine how pre-sport games impact the psychomotor development of sixth-grade children at the Pensionado Americano Educational Unit. The 3JS Test was used as a data collection method; it is a battery of physical tests designed to evaluate specific motor skills in athletes. The methodology is descriptive and propositional, focusing on formulating and proposing solutions or interventions to address specific problems or improve current situations. This type of research describes reality and seeks to generate positive changes by implementing concrete proposals based on the findings obtained. The research is classified as quasi-experimental because it uses a pre-test and post-test design to collect data before and after the intervention. This type of research allows for measuring the effects of the pre-sport games program on the psychomotor development of children without the need for random assignment of participants. The evaluation of psychomotor development through pre-test and post-test showed significant progress in the children's psychomotor skills. The results indicated notable agility, coordination, balance, and movement precision improvements. These findings confirm the effectiveness of the pre-sport games program as a valuable pedagogical tool for psychomotor development in educational settings